2020
DOI: 10.1093/mnras/staa2536
|View full text |Cite
|
Sign up to set email alerts
|

On the cavity size in circumbinary discs

Abstract: How does the cavity size in circumbinary discs depend on disc and binary properties? We investigate by simulating disc cavities carved by binary companions using smoothed particle hydrodynamics (SPH). We find that a cavity is quickly opened on the dynamical time, while the cavity size is set on the viscous time. In agreement with previous findings, we find long term cavity sizes of 2–5 times the binary semi-major axis, increasing with eccentricity and decreasing with disc aspect ratio. When considering binarie… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 65 publications
1
38
0
Order By: Relevance
“…size and eccentricity, has been documented in numerical works (Thun et al 2017;Hirsh et al 2020;Ragusa et al 2020). Results suggested that the gas cavity profile progressively steepens to match the theoretical prediction (Hirsh et al 2020). A large disc thickness (we recall in this case 𝐻/𝑅 = 0.2) and viscosity 𝛼 ss appear to prevent the disc eccentricity to reach large values in the gas (Ragusa et al 2020), as it would be instead expected for lower disc aspect ratios (Thun et al 2017;Miranda et al 2017).…”
Section: Kinematics and Evolution Of The System Propertiessupporting
confidence: 58%
See 1 more Smart Citation
“…size and eccentricity, has been documented in numerical works (Thun et al 2017;Hirsh et al 2020;Ragusa et al 2020). Results suggested that the gas cavity profile progressively steepens to match the theoretical prediction (Hirsh et al 2020). A large disc thickness (we recall in this case 𝐻/𝑅 = 0.2) and viscosity 𝛼 ss appear to prevent the disc eccentricity to reach large values in the gas (Ragusa et al 2020), as it would be instead expected for lower disc aspect ratios (Thun et al 2017;Miranda et al 2017).…”
Section: Kinematics and Evolution Of The System Propertiessupporting
confidence: 58%
“…Long term evolution of the cavity properties, i.e. size and eccentricity, has been documented in numerical works (Thun et al 2017;Hirsh et al 2020;Ragusa et al 2020). Results suggested that the gas cavity profile progressively steepens to match the theoretical prediction (Hirsh et al 2020).…”
Section: Kinematics and Evolution Of The System Propertiesmentioning
confidence: 88%
“…Harris et al 2012) or multiple Jovian planets (Dodson-Robinson & Salyk 2011; Close 2020). A binary companion can clear a cavity of 2-5 times the binary separation (Artymowicz & Lubow 1994;Hirsh et al 2020), so for transition disk cavities of ∼25-100 au we are interested in binary companions at ∼10-50 au separation. This is further discussed in Section 6.5.…”
Section: Observed Disk Morphologies Exoplanet Demographicsmentioning
confidence: 99%
“…We assume that the disk with i d = 54.6 • and Ω d = 53.0 • has its NW side closer to the observer. Following this definition, due to the 180 • ambiguity of Ω b , we obtain two possible solutions (see Figure 10 Theoretical models of tidal truncation predict that the inner edges (r in ) of circumbinary disks would be located at 2-3a for binary orbits with moderate eccentricity and when coplanar with their surrounding disks (Artymowicz & Lubow 1994;Hirsh et al 2020). In the case of misalignment, r in /a would however have a complicated dependence on the mutual inclination, orbital eccentricity, and binary mass ratio.…”
Section: V892 Taumentioning
confidence: 99%
“…Depending on the stellar configuration, multiple disks could be present in a binary system, including a circumbinary disk orbiting around the binary and disks surrounding individual stellar components. Dynamical interactions between stars and disks tend to truncate the disks (e.g., creating an inner cavity in a circumbinary disk), reduce their masses, and shorten their lifetimes (e.g., Artymowicz & Lubow 1994;Breslau et al 2014;Hirsh et al 2020). For example, disks in close binaries (separation < 30 − 40 au) have fainter millimeter emission (Jensen et al 1996;Harris et al 2012;Akeson et al 2019), with a lower frequency presenting accretion signatures and/or near-infrared excess emission (Bouwman et al 2006;Cieza et al 2009;Kraus et al 2012), compared to disks around single stars.…”
Section: Introductionmentioning
confidence: 99%